Pengaruh Kesadaran Wajib Pajak, Tingkat Kepercayaan Kepada Pemerintah, dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak UMKM - Rizalti, Suri Meylinda; Iskandar, Diah (Universitas Gorontalo, 2025)
This research aims to obtain empirical evidence about the influence of Taxpayer awareness, level of trust in the government and tax sanctions on MSME Taxpayer compliance. The population in this research is MSME Taxpayers in the Jagakarsa District area, South Jakarta. The sampling technique used the Nonprobability Sampling method with a purposive sampling approach. The sample used amounted to 97 respondents. The data analysis method used in the research is descriptive statistics and hypothesis testing using SmartPLS 4. The results of the study show that taxpayer awareness and tax sanctions has a positive and significant effect on taxpayer compliance, while level of trust in the government do not have a significant effect on taxpayer compliance.